El graffiti: expresión cultural como parte de la comunicación humana y su influencia en los jóvenes de la ciudad de Loja, periodo julio-diciembre de 2012. Propuesta alternativa - Agurto Briceño, Telmo Cristobal (2015)
Cultural expression as part of human communication and its influence on the youth of the city of Loja, for it was necessary to analyze: In this paper an amalgam of factors and reasons that are related to the topic called, " graffiti is presented direct at the place where the event, theme of inquiry, in order to know how this activity generates a series of effects on young people who grow this action was detected. Likewise, it will determine the level of knowledge among young people in relation to the influence it has on the community. In this context, it was found that the graffiti constitute a form of cultural expression and especially of human communication, this is confirmed with the results obtained in the field, and demonstrate that this situation has not been understood by the community, because the spaces looking graffiti artists do under express freely, but really not enough, because they have to draw their ideas or in walls or walls, always covered in the darkness of night. The general and specific objectives that are accompanied by the interpretations were verified with the results from the implementation of surveys and interviews, where you can find that young lojanos practice this art with the sole purpose of telling the rest of the conglomerate way how to see reality. Keywords: The Graffiti, Urban Alternative Communication, Cultural Expression, Graffiti, Influence Youth.